Komunikasi Pemasaran Tikar Purun Desa Menang Raya Kecamatan Pedamaran - Maharani, Dwi; Aprianto, Ricky (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to determine the marketing communication of purun mats in the sub-district of Pedamaran. The theory used is Integrated Marketing Communication (IMC). The research method used a descriptive qualitative approach, then the object of research was in the sub-district of Pendamaran while the research subjects were village heads, community leaders, purun mat craftsmen and the community. The result of this study is that marketing that is still traditional relying on middlemen (people to people) cannot be known directly by many people and is an obstacle to the progress of mat weaving marketing and through existing networks, for example, brought to collectors to be taken out of town and only use Facebook social media in marketing